2018
DOI: 10.1387/ijdb.170260rl
|View full text |Cite
|
Sign up to set email alerts
|

Pou3f transcription factor expression during embryonic development highlights distinct pou3f3 and pou3f4 localization in the Xenopus laevis kidney

Abstract: The POU (Pit-Oct-Unc) genes encode a large transcription factor family comprising 6 classes (pou1f to pou6f ) involved in many developmental processes, such as cell commitment and differentiation. The pou3f class contains four members (pou3f1, pou3f2, pou3f3, pou3f4) characterized by expression in ectodermal tissue derivatives, such as nervous system and otic vesicle, during mammalian development. In order to obtain insights into the potential conservation of this class of transcription factors in vertebrates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…We also confirmed coexpression by performing whole mount in situ hybridization (WISH) analysis of stage 12 (late gastrula) and stage 14 (neurula) Xenopus embryos demonstrating that sox11 expression overlaps with ngn2 anpou3f2 ( Figure S2). In line with our WISH data, previous research shows pou3f2 expression is not detectable at stage 12 by WISH due to low transcript levels, but is visible at stage 14 in the anterior neural plate (37).…”
Section: Sox11 and Potential Partners Are Co-expressed In Distinct Cesupporting
confidence: 92%
See 1 more Smart Citation
“…We also confirmed coexpression by performing whole mount in situ hybridization (WISH) analysis of stage 12 (late gastrula) and stage 14 (neurula) Xenopus embryos demonstrating that sox11 expression overlaps with ngn2 anpou3f2 ( Figure S2). In line with our WISH data, previous research shows pou3f2 expression is not detectable at stage 12 by WISH due to low transcript levels, but is visible at stage 14 in the anterior neural plate (37).…”
Section: Sox11 and Potential Partners Are Co-expressed In Distinct Cesupporting
confidence: 92%
“…We also show that xSox11 interacts with xPou3f2 (also known as Brn2 or Oct7), however, this relationship is not well defined in Xenopus neural plate development and has various expression patterns and functions across species. Pou3f2 is robustly expressed in stage 14 neurulae but is not detectable in stage 12 gastrulae ( Figure SA1) (37). In rat neural precursor cells, Pou3f2 co-localizes with progenitor cell markers and is downregulated upon differentiation (44).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Brn4 has been detected in the embryonic pancreas and adult glucagon cells (23,24). A previous study investigating the role of the POU3 gene during development in Xenopus laevis found that Brn4 was expressed in the embryonic neural tube, brain, developmental ear vesicles, distal renal tubules and connective tubules (11). RNA sequencing results of the genome-wide analysis of 272 mouse cell and tissue types revealed the widespread expression of Brn4 during nervous system development, including within the neural crest, neuroectoderm, hypothalamus, pituitary, hippocampus and inner ear (5).…”
Section: Protein Molecular Structure and Tissue Distributionmentioning
confidence: 99%
“…Brn1 is involved in the development of the central nervous system, and its loss-of-function mutations were identified to cause developmental delays, intellectual disability and impairments in language skills (10). It was also found to be expressed in the developing kidney (11). In previous studies, Brn1 knockout mice were discovered to have neurological defects, including locomotor and auditory impairments, but also a thicker ascending loop of the limb of Henle and decreased numbers of nephrons, thus resulting in renal failure and perinatal death (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…POU3F4 , along with the gene EPHA4 , is also important in spiral ganglion fasciculation in the spiral ligament and essential for correct ganglion innervation ( Coate et al 2012 ). It is also expressed in the developing brain and kidney ( Petersen et al 2008 ; Cosse-Etchepare et al 2018 ) although functional studies within these organs are lacking. Mutations within POU3F4 lead to a severe mixed or sensorineural hearing loss, which in most patients affect all audiometric frequencies and can be progressive ( Petersen et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%